The Multifaceted Function of Granzymes in Sepsis: Some Facts and a Lot to Discover - Garzón-Tituaña, Marcela; Arias, Maykel A.; Sierra-Monzón, José L.; Morte-Romea, Elena; Santiago, Llipsy; Ramirez-Labrada, Ariel; Martinez-Lostao, Luis; Paño-Pardo, José R.; Galvez, Eva M.; Pardo, Julián (Frontiers in Immunology, 2020)
Sepsis is a serious global health problem. In addition to a high incidence, this syndrome has a high mortality and is responsible for huge health expenditure. The pathophysiology of sepsis is very complex and it is not well understood yet. However, it is widely accepted that the initial phase of sepsis is characterised by a hyperinflammatory response while the late phase is characterised by immunosuppression and immune anergy, increasing the risk of secondary infections. Granzymes (Gzms) are a family of serine proteases classified according to their cleavage specificity. Traditionally, it was assumed that all Gzms acted as cytotoxic proteases. However, recent evidence suggests that GzmB is the one with the greatest cytotoxic capacity, while the cytotoxicity of others such as GzmA and GzmK is not clear. Recent studies have found that GzmA, GzmB, GzmK and GzmM act as pro-inflammatory mediators. Specially, solid evidences show that gzmA and gzmK function as extracellular proteases that regulate the inflammatory response irrespectively of its ability to induce cell death. Indeed, studies in animal models indicate that gzmA is involved in the Cytokine Release Syndrome characteristic of sepsis. Moreover, the GZM family also could regulate other biological processes involved in sepsis pathophysiology like the coagulation cascade, platelet function, endothelial barrier permeability and in addition, could be involved in the immunosuppressive stage of sepsis. In this review, we provide a comprehensive overview on the contribution of these novel functions of Gzms to sepsis and the new therapeutic opportunities emerging from targeting these proteases for the treatment of this serious health problem.